Broadband THz wave generation in organic benzothiazolium crystals at MHz repetition rates [Invited] - Puc, Uros; Yang, Jeong A.; Kim, Deokjoong; Kwon, O. Pil; Jazbinsek, Mojca (Optical Materials Express, 2023)
We present broadband terahertz wave generation based on benzothiazolium crystals at a 100 MHz repetition rate. Among various benzothiazolium crystals, we chose PMB-4TFS (2-(4-(4-(hydroxymethyl)piperidin-1-yl)styryl)-3-methylbenzothiazol-3-ium 4-(trifluorome-thyl)benzenesulfonate) due to its large macroscopic optical nonlinearity, good crystal characteristics, and suppressed molecular phonon vibrations. When pumped at the telecommunication wavelength of 1560 nm, the generated THz spectrum covers up to ∼15 THz and the corresponding THz amplitude for a 0.29 mm thick crystal at normal incidence is by more than one order of magnitude higher compared to the inorganic standard, 1.0 mm thick ZnTe generator crystal.
Keywords: Benzenesulfonates; Broadband terahertz; Crystal characteristics; Optical nonlinearity; Organics; Repetition rate; Terahertz wave generation; Terahertz-wave generation; THz waves; Wave generation